2015
DOI: 10.1111/josh.12244
|View full text |Cite
|
Sign up to set email alerts
|

One Size (Never) Fits All: Segment Differences Observed Following a School‐Based Alcohol Social Marketing Program

Abstract: BACKGROUND According to commercial marketing theory, a market orientation leads to improved performance. Drawing on the social marketing principles of segmentation and audience research, the current study seeks to identify segments to examine responses to a school‐based alcohol social marketing program. METHODS A sample of 371 year 10 students (aged: 14–16 years; 51.4% boys) participated in a prospective (pre‐post) multisite alcohol social marketing program. Game On: Know Alcohol (GO:KA) program included 6, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 38 publications
1
38
2
Order By: Relevance
“…Demographic approaches often use information such as gender, age, and income as proxies for unobservable variables that can predict behaviour (Mowen & Minor, ; Park & Lee, ; Ukenna, Nkamnebe, Nwaizugbo, Moguluwa, & Olise, ). Yet simply segmenting on demographic variables has received criticism (Dietrich, Rundle‐Thiele, Leo, & Connor, ), as meaningful segments can be identified on the basis of at least four segmentation bases: demographic, psychographic, geographic, and behavioural variables (Kotler, ). Once segments are formed, a segment(s) that is the most measurable, accessible, sustainable, and substantial should be targeted for the best return on investment (Kotler, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic approaches often use information such as gender, age, and income as proxies for unobservable variables that can predict behaviour (Mowen & Minor, ; Park & Lee, ; Ukenna, Nkamnebe, Nwaizugbo, Moguluwa, & Olise, ). Yet simply segmenting on demographic variables has received criticism (Dietrich, Rundle‐Thiele, Leo, & Connor, ), as meaningful segments can be identified on the basis of at least four segmentation bases: demographic, psychographic, geographic, and behavioural variables (Kotler, ). Once segments are formed, a segment(s) that is the most measurable, accessible, sustainable, and substantial should be targeted for the best return on investment (Kotler, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social marketing program designers have begun to apply segmentation theory to understand group differences in study populations in diverse fields including obesity (McLeay & Oglethorpe, ; Olds, Thomas, Lewis, & Petkov, ), alcohol (Dietrich, Rundle‐Thiele, Leo et al, ; Dietrich, Rundle‐Thiele, Schuster et al, ), and physical activity (Rundle‐Thiele, Kubacki, Tkaczynski, & Parkinson, ). Segmentation has been considered as a key ingredient for designing more targeted social marketing programs (Andreasen, ; Lefebvre & Flora, ; Rundle‐Thiele et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This objective will be achieved through two approaches: (1) by investigating the impact of intrinsic and extrinsic religiosity on consumer ethics and (2) by segmenting consumers' religiosity and exploring differences between the segments. Segmentation is an effective ways to identify differences among groups, which will drive how we approach a solution (Dietrich et al 2015). Therefore, the present study contributes to the consumer ethics literature by examining the role of religiosity in determining ethical beliefs.…”
Section: Introductionmentioning
confidence: 97%
“…Typically, alcohol education programs targeted at young people are conducted in school settings and delivered in a didactic teacher-focused approach (Lee et al, 2016). The program content is expert-driven, that is, evidenced-based and universal messages are applied to a generalized target audience (Dietrich et al, 2015, Newton et al, 2016. Recent studies, however, have indicated that this 'one fits all' approach might not be effective (Lee et al, 2016, Onrust et al, 2016: First, a generalized approach means that young people might not identify with the communicated message, leading to little engagement with or even rejection of the program.…”
Section: Literature Alcohol Education -Exploring New Approachesmentioning
confidence: 99%